Conceptual Analysis: The Charcoal-Agriculture Nexus to Understand the Socio-Ecological Contexts Underlying Varied Sustainability Outcomes in African Landscapes - Iiyama, Miyuki; Neufeldt, Henry; Njenga, Mary; Derero, Abayneh; Ndegwa, Geoffrey M.; Mukuralinda, Athanase; Dobie, Philip; Jamnadass, Ramni; Mowo, Jeremias (Frontiers in Environmental Science, 2017)
The production of charcoal is an important socio-economic activity in sub-Saharan Africa (SSA). Charcoal production is one of the leading drivers of rural land-use changes in SSA, although the intensity of impacts on the multi-functionality of landscapes varies considerably. Within a given landscape, charcoal production is closely interconnected to agriculture production both as major livelihoods, while both critically depend on the same ecosystem services. The interactions between charcoal and agricultural production systems can lead to positive synergies of impacts, but will more often than not result in trade-offs and even vicious cycles. Such sustainability outcomes vary from one site to another due to the heterogeneity of contexts, including agricultural production systems that affect the adoption of technologies and practices. Trade-offs or cases of vicious cycles occur when one-off resource exploitation of natural trees for charcoal production for short-term economic gains permanently impairs ecosystem functions. Given the fact that charcoal, as an important energy source for the growing urban populations and an essential livelihood for the rural populations, cannot be readily substituted in SSA, there must be policies to support charcoal production. Policies should encourage sustainable technologies and practices, either by establishing plantations or by encouraging regeneration, whichever is more suitable for the local environment. To guide context-specific interventions, this paper presents a new perspective - the charcoal-agriculture nexus - aimed at facilitating the understanding of the socio-economic and ecological interactions of charcoal and agriculture production. The nexus especially highlights two dimensions of the socio-ecological contexts: charcoal value chains and tenure systems. Combinations of the two are assumed to underlie varied socio-economic and ecological sustainability outcomes by conditioning incentive mechanisms to affect the adoption of technologies and practices in charcoal and agriculture productions. Contrasting sustainability outcomes from East Africa are presented and discussed through the lens of the charcoal-agriculture nexus. The paper then concludes by emphasizing the importance of taking into account the two-dimensional socio-ecological contexts into effective policy interventions to turn charcoal-agriculture interactions into synergies.